Krænkelse, moderstolthed og vrede islændinge: Mediedebatten om koloniudstillingen 1905 - Nielsen Gremaud, Ann-Sofie (K&K - Kultur og Klasse, 2022)
In the early summer of 1905, a colonial exhibition opened in the Tivoli Gardens in Copenhagen, where visitors could meet people and see objects from more distant parts of the Danish kingdom: the West Indies, Greenland, the Faroe Islands and Iceland. Both before and during the exhibition, a dispute arose in the Danish and Icelandic media about the reasonableness of Iceland being part of such a setting. The disagreement was about the representational logic that was the foundation of the exhibition, about the title of the exhibition, and about whether Iceland belonged in the “company” that the other countries constituted. In this article, the author draws attention to the emotionality that characterized the debate that Danish and Icelandic writers took part in. The examples show how the Icelanders’ protests against the exhibition are framed as unreasonably emotional and the Icelanders as sensitive and ungrateful. Thus, the author argues that there are similarities with the strategies used in contemporary debates about reasonable responses to violations and insults in Scandinavia.